KEPULAUAN MENTAWAI DAN PENDIDIKAN INKLUSIF - Irdamurni Irdamurni; Mega Iswari; Asep Ahmad Sopandi (Jurnal Pendidikan Kebutuhan Khusus, 2019)
The problem in the pejat old village, namely the number of children with special needs who have not had the opportunity in proper education, this is in the teachers do not have the competence in spending children with special needs in inclusive settings. The purpose of this service is to increase teacher competence in improving inclusive education in primary schools. The method in organizing PKM uses multiple methods, namely lecture and question and answer methods for inclusive education materials and children with special needs. Furthermore, using demonstration methods, methods of practice and practice on material on how to conduct discussions and assessments of children with special needs, as well as developing learning programs (RPP) in inclusive settings, all training implementation uses the principles of learning for adults (andragogic). The implementation of this PKM received a very enthusiastic welcome from the teachers. It is expected that trainees can provide their experiences to other teachers in their respective schools, and be able to work closely with SLB teachers and parents of children with special needs in the learning of children in inclusive schools.